POSSIBLE USE OF LASERS FOR CLEAVAGE OF PHENOLS TILL BASE SUBSTANCES (REVIEW) - Zarecka, Diāna; Lazov, Lyubomir (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2023)
The purpose of this review article is to explain the hazards of phenol and phenol compounds to human health and the environment. To describe where and how phenol and its compounds occur, especially in industrial effluents. To study the possibility of using laser technologies for phenol cleavage, as well as for the treatment of industrial wastewater from phenol compounds. Removal of phenol and its compounds using biological wastewater treatment process is widely used worldwide. This method is cost-effective and environmentally friendly. On the other hand, exceeding the tolerable phenol concentration, which is individual for each biological treatment plant, may result in severe intoxication and lead to death of activated sludge system. Thus, the biological treatment process of industrial wastewater is halted until the phenol concentration is reduced to an acceptable level and the microorganisms have time to recover. Such a procedure can be time consuming and unpredictable due to the susceptibility of microorganisms to changing conditions. Based on this, sources of literature have been studied that could help to understand which laser equipment can be used to cleave a phenolic compound or benzene ring to simpler compounds.